2019
DOI: 10.3390/ijms20071551
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms for Coping with Al Toxicity in Plants

Abstract: Aluminum (Al) toxicity is one of the major constraints to agricultural production in acid soils. Molecular mechanisms of coping with Al toxicity have now been investigated in a range of plant species. Two main mechanisms of Al tolerance in plants are Al exclusion from the roots and the ability to tolerate Al in the roots. This review focuses on the recent discovery of novel genes and mechanisms that confer Al tolerance in plants and summarizes our understanding of the physiological, genetic, and molecular basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 127 publications
(184 reference statements)
0
45
0
Order By: Relevance
“…acetic acid). A very recent study however identified a bidirectional aluminum-malate transporter, which may be also involved in root malate uptake 42 . Results here presented, reveal that tomato plants are able to take up citrate from the uptake solution (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…acetic acid). A very recent study however identified a bidirectional aluminum-malate transporter, which may be also involved in root malate uptake 42 . Results here presented, reveal that tomato plants are able to take up citrate from the uptake solution (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Homologous MATE proteins with similar citrate transport functions have been identified from wheat 12 , maize 13 , sorghum 14 , rice 15 , and Arabidopsis 16 . In addition to the citrate transporter MATE, another Al-activated malate transporter (ALMT) has also been reported in many plants and is associated with the malate-mediated Al detoxification 17,18 . Genetic studies on the Al-tolerance mechanism in grain legumes are still very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Plants utilize two different mechanisms to develop Al tolerance: the Al exclusion to prevent/reduce the entry of the ions into root-tip cells and the ability to tolerate internalized Al 63,64 . Hematoxylin is a dye which forms a complex with Al, and the color intensity of stained root apices can be used as a measurement of the amount of Al accumulated/internalized in root-tip cells 43,44 .…”
Section: Discussionmentioning
confidence: 99%